Konsep Pembelajaran Keterampilan Aktif Reseptif Bahasa Arab pada Kelas VIII E di Madrasah Tsanawiyah Negeri 2 Purwakarta - Sadili, Sadili; Qosim, Nanang (STAINI Press, 2024)
This study aims to uncover and describe the learning of Arabic receptive active skills in MTsN 2 Purwakarta. This study uses a qualitative approach with a type of case study. The data collection technique in this study has two data sources, namely primary and secondary, which are collected through observation, interviews, and documentation. Data analysis is carried out with inductive techniques and presented with descriptive techniques. The findings of this study are that the teaching of Arabic receptive active skills of each student is required to read Arabic texts and memorize language vocabulary, students read Arabic texts in front of other students, accentuate Arabic conversations in front of other participants. There are two students who cannot read Arabic writing and seven students who read it are still in the category of stammering, Students have study groups, inadequate learning facilities such as laptops, projectors, sound systems and other supporting equipment.